Vegetable Outlook 2007 - John J. VanSickle (EDIS)
FE681, a 4-page illustrated fact sheet by John J. VanSickle, provides short- and long- term outlook for demand, supply, international trade, and regulatory issues facing Florida vegetable growers. Published by the UF Department of Food and Resource Economics, December 2006.